Alternative Use for Spectra MRSA Chromogenic Agar in Detection of Methicillin-Resistant Staphylococcus aureus from Positive Blood Cultures - Peterson, Jess F. (American Society for Microbiology (ASM), 2010)
Spectra MRSA agar (Remel, Lenexa, KS), a novel chromogenic medium originally developed to detect methicillin-resistant Staphylococcus aureus (MRSA) from nasal swabs, was evaluated in this multicenter study for the detection of MRSA from positive blood cultures exhibiting Gram-positive cocci upon initial Gram staining.